The relationship between exercise motivation and exercise behavior in college students: The chain-mediated role of exercise climate and exercise self-efficacy - Zhao, Yu Shun; Ma, Qi Shuai; Li, Xing Yi; Guo, Ke Lei; Chao, Liu (Frontiers in Psychology, 2023)
Objective: This study explored the relationship between college students' physical activity motivation and exercise behavior and constructed a chain mediation model through the mediating roles of exercise climate and exercise self-efficacy. Methods: By random sampling, 1,032 college students were investigated using the Exercise Motivation Scale, Physical Exercise Rating Scale, Exercise Climate Scale, and Exercise Self-Efficacy Scale. Results: (1) There was a significant positive correlation between exercise motivation and exercise behavior (r = 0.240, p < 0.01), and the direct paths of exercise motivation to exercise behavior were significant (β = 0.068, t = 0.040, p < 0.01). (2) Exercise motivation could positively predict exercise climate (β = 0.373, t = 0.061, p < 0.01) and exercise self-efficacy (β = 0.174, t = 0.039, p < 0.01), and exercise climate could positively predict exercise behavior (β = 0.302, t = 0.051, p < 0.01). Exercise self-efficacy could predict exercise behavior positively (β = 0.190, t = 0.048, p < 0.01). (3) exercise climate and exercise self-efficacy play a significant mediating role between exercise motivation and exercise behavior. The mediation effect is specifically composed of indirect effects generated by three paths: exercise motivation → exercise climate → exercise behavior (mediating effect value: 0.113); exercise motivation → exercise self-efficacy → exercise behavior (mediating effect value: 0.033); exercise motivation → exercise climate → exercise self-efficacy → exercise behavior (mediating effect value: 0.027). Conclusion: (1) Physical exercise motivation can significantly predict exercise climate, exercise self-efficacy, and exercise behavior, which means that physical exercise motivation may contribute to improving exercise climate, exercise self-efficacy, and exercise behavior. (2) Physical exercise motivation can not only directly influence exercise behavior but also indirectly influence it through the separate mediating effects of exercise climate and exercise self-efficacy and the chain mediating effect of exercise climate and exercise self-efficacy, further explaining the reasons for the effect of physical exercise motivation on college students' exercise behavior, which is important for promoting college students' exercise behavior.